Plasma fetuin‐A concentration, genetic variation in the AHSG gene and risk of colorectal cancer. Issue 4 (5th February 2015) - Nimptsch, Katharina; Aleksandrova, Krasimira; Boeing, Heiner; Janke, Jürgen; Lee, Young‐Ae; Jenab, Mazda; Kong, So Yeon; Tsilidis, Konstantinos K.; Weiderpass, Elisabete; Bueno‐De‐Mesquita, H. B(as); Siersema, Peter D.; Jansen, Eugène H.J.M.; et al.
<x xml:space="preserve">Abstract</x> Fetuin‐A, also referred to as α2‐Heremans‐Schmid glycoprotein (AHSG), is a liver protein known to inhibit insulin actions. Hyperinsulinemia is a possible risk factor for colorectal cancer; however, the role of fetuin‐A in the development of colorectal cancer is unclear. We investigated the association between circulating fetuin‐A and colorectal cancer risk in a nested case–control study within the European Prospective Investigation into Cancer and Nutrition. Fetuin‐A concentrations were measured in prediagnostic plasma samples from 1, 367 colorectal cancer cases and 1, 367 matched controls. In conditional logistic regression models adjusted for potential confounders, the estimated relative risk (95% confidence interval) of colorectal cancer per 40 µg/mL higher fetuin‐A concentrations (approximately one standard deviation) was 1.13 (1.02–1.24) overall, 1.21 (1.05–1.39) in men, 1.06 (0.93–1.22) in women, 1.13 (1.00–1.27) for colon cancer and 1.12 (0.94–1.32) for rectal cancer. To improve causal inference in a Mendelian Randomization approach, five tagging single nucleotide polymorphisms of the AHSG gene were genotyped in a subset of 456 case–control pairs. The AHSG allele‐score explained 21% of the interindividual variation in plasma fetuin‐A concentrations. In instrumental variable analysis, genetically raised fetuin‐A was not associated with colorectal cancer risk (relative risk per 40 µg/mL genetically determined higher fetuin‐A was 0.98, 95% confidence interval: 0.73–1.33). The findings of our study indicate a modest linear association between fetuin‐A concentrations and risk of colorectal cancer but suggest that fetuin‐A may not be causally related to colorectal cancer development.